2008
DOI: 10.1021/es8016717
|View full text |Cite
|
Sign up to set email alerts
|

Stratification Structure of Sludge Flocs with Implications to Dewaterability

Abstract: Sludge dewatering has proven to be an effective method to reduce the volume of sludge. In this study, a novel stratification approach aimed at better understanding the factors influencing the sludge dewaterability (as determined by capillary suction time, CST) was developed. The sludge flocs from 14 different full-scale wastewater treatment plants (WWTPs), including sewage, leachate, industry, and special-source sludge, were stratified through centrifugation and ultrasound into five layers: (1) supernatant, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(131 citation statements)
references
References 24 publications
7
122
1
1
Order By: Relevance
“…The SEPS concentration was reduced from 2.95 mgDOC/ gTSS to 1.64, 1.43 and 2.30 mgDOC/gTSS with PACl, Fe 3þ and PAM addition respectively, revealing that FeCl 3 was more effective in removing organic matters in sludge. It was suggested that ferric ions exhibited higher affinity to protein-like substances (Yu et al, 2008). In addition, according to our previous report, protein like substances in SEPS fraction were found to be the main influencing factor of sludge filtration dewatering performance (Zhang et al, 2015c).…”
Section: Fe-sem Analysismentioning
confidence: 78%
See 1 more Smart Citation
“…The SEPS concentration was reduced from 2.95 mgDOC/ gTSS to 1.64, 1.43 and 2.30 mgDOC/gTSS with PACl, Fe 3þ and PAM addition respectively, revealing that FeCl 3 was more effective in removing organic matters in sludge. It was suggested that ferric ions exhibited higher affinity to protein-like substances (Yu et al, 2008). In addition, according to our previous report, protein like substances in SEPS fraction were found to be the main influencing factor of sludge filtration dewatering performance (Zhang et al, 2015c).…”
Section: Fe-sem Analysismentioning
confidence: 78%
“…Moreover, some researchers reported that only the LB-EPS was related to the sludge dewaterability (Li and Yang, 2007;Ramesh et al, 2006;Raynaud et al, 2012). Yu et al (2008) suggested that sludge floc was composed by five fractions: supernatant, slime, LB-EPS, TBEPS, and pellet, and the sludge dewatering performance was mainly influenced by soluble EPS characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…suggested that the high content of protein in SEPS was always detrimental to sludge filterability (Zhang et al, 2014b(Zhang et al, , 2015c(Zhang et al, , 2015d. Yu et al (2008) also found that the sludge dewaterability correlated well with proteins content in the supernatant and LB-EPS rather than that in TB-EPS fraction. As mentioned above, HPSEC analysis further confirmed that the waste activated sludge dewatering performance was enhanced by TSC 0.5 treatment was mainly related to its higher binding capacity with protein-like substances.…”
Section: Fig 4 Effects Of Tscs Dosages On Concentrations Of Differementioning
confidence: 79%
“…Recently, Li and Yang (2007) suggested that the spatial distribution and chemical compostion of EPS had more significant effects on sludge dewatering property, and sludge dewatering performance was mainly dependent on content of loosely-bound EPS (LB-EPS) rather than that of tightly bound EPS (TB-EPS). Furhter, Yu et al (2008) demonstrated that soluble EPS also played an important role in sludge dewatering process. Zhang et al (2015a) suggested that change in concentration and compostion of soluble EPS fraction caused fluctuation of sludge dewatering behavior with time.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that pH had a more significant effect on proteins which were obviously solubilized and released into sludge bulk at pH less than 5. According to many previous reports, proteins in LB-EPS and soluble EPS were the major factors affect- ing sludge dewatering behavior [18,26]. It was found that higher concentration of extractable EPS, especially high protein concentration was always related to poor sludge dewatering performance.…”
Section: Impact Of Ph On Eps Properties With/without Ferrate Treatmenmentioning
confidence: 95%